Pengaruh Konsentrasi NaOH terhadap Sifat-Sifat Karaginan Eucheuma cottonii dari Karimun Jawa dan Madura - Widiastuti HN (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Carrageenan Eucheuma cottonii is a species of seaweed having high economic values that is grows in Indonesia. The main constraint needs to be concerned were decreasing of carrageenan rendement values affected the quality and quantity in downstream industry. The aim of this study was to find out optimal carrageenan rendement with NaOH concentrate variation from Karimun Jawa and Madura areas. The method applied experimental using factorial plan design. The treatments given were the different location, the color variation of of E. cottonii and variation NaOH concentration to extract the carrageenan. The result shows that different carrageenan quality and carrageenan contain of red and green E. cottonii from different sample taking location. The application of NaOH as much as 5% for carrageenan extraction produced the highest yield, gel strength and gelling temperature but gives lowest viscosity.